2022
DOI: 10.3390/app12178593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rehabilitation on Fatigue in Post-COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: The post-COVID-19 syndrome may affect patients after the COVID-19 post-acute phase. In particular, the 69% of patients reported persistent fatigue at the discharge. To date, no clear data are available regarding the most effective rehabilitative approaches for the treatment of this condition. Thus, this systematic review aimed to evaluate the rehabilitation treatment’s efficacy on fatigue in post-COVID-19 patients. We systematically searched PubMed, Scopus, and Web of Science databases to find longitudinal stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Delgado-Alonso et al [ 14 ] reported a relationship between post-COVID patients who were not able to return to work and high levels of fatigue. The first results verified the positive effects of rehabilitation on fatigue [ 37 , 55 , 56 , 60 ]. Fatigue symptoms decreased significantly after six weeks of an outpatient pulmonary rehabilitation program [ 37 ].…”
Section: Introductionmentioning
confidence: 69%
“…Delgado-Alonso et al [ 14 ] reported a relationship between post-COVID patients who were not able to return to work and high levels of fatigue. The first results verified the positive effects of rehabilitation on fatigue [ 37 , 55 , 56 , 60 ]. Fatigue symptoms decreased significantly after six weeks of an outpatient pulmonary rehabilitation program [ 37 ].…”
Section: Introductionmentioning
confidence: 69%
“…SF36v2 is a widely used scale incorporated in a large spectrum of research and one of the first to be utilized for COVID-19-related studies [14]. Similarly, EQ5D5L and FACIT-F have been applied in various studies internationally regarding the effects of the COVID-19 pandemic, among others [20][21][22][23]. Additionally, PCFSS is a recently created tool, aiming for quick assessment of possible long-term loss of function resulting from a SARS-CoV-2 infection [24,25].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Scientific questions on the long-term impact of COVID-19, specifically on matters such as the diagnosis, as well as in its definition, still require more research [ 2 ]. COVID-19 may have detrimental sequelae even after the post-acute phase, thereby depicting a new pathological condition: the “post-COVID-19 syndrome (PCS)” or “long COVID-19” [ 3 ]. Long COVID-19, also called post COVID-19 condition, was defined as a condition that occurs in individuals with a history of probable or confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.…”
Section: Introductionmentioning
confidence: 99%